2020
DOI: 10.4103/jfmpc.jfmpc_853_20
|View full text |Cite
|
Sign up to set email alerts
|

Level of knowledge of mothers (18-35 years of age) of under 5 children regarding ORS therapy

Abstract: Context: Diarrhea is a preventable cause of under 5 years of mortality. Mothers are a primary caregiver for children at home during an illness so this study was planned. Aims: To estimate the demographic variables and level of knowledge of mothers (18-35 years of age) of under 5 children regarding ORS therapy. Settings and Design: The study was conducted in selected rural areas Chandandih (a small village in Raipur district). There is one sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our findings align with those of another study where the researchers reported a low level of awareness regarding home care for diarrhea, consistent with the relatively limited knowledge observed concerning ORS and home-based diarrhea management 14 . These findings underscore the importance of educational efforts to enhance awareness and knowledge among caregivers, particularly regarding the use of ORS as a vital tool in managing diarrhea effectively and reducing related morbidity and mortality [15][16][17] .…”
Section: Discussionmentioning
confidence: 86%
“…Our findings align with those of another study where the researchers reported a low level of awareness regarding home care for diarrhea, consistent with the relatively limited knowledge observed concerning ORS and home-based diarrhea management 14 . These findings underscore the importance of educational efforts to enhance awareness and knowledge among caregivers, particularly regarding the use of ORS as a vital tool in managing diarrhea effectively and reducing related morbidity and mortality [15][16][17] .…”
Section: Discussionmentioning
confidence: 86%
“…The results of the needs assessment were consistent with other studies. A study showed that 63.34 percent of mothers had little knowledge on ORS therapy (Divasha et al, 2020). The findings of another study indicated lack of competence of mothers in dealing with diarrhoea and diet management due to moderate level of knowledge and practice (Khalili et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similar low levels of knowledge and practices of mothers regarding ORS preparation are shown in previous evaluations conducted in similar settings. [ 20 , 21 ]…”
Section: Discussionmentioning
confidence: 99%